Robotic Eye-in-hand Calibration in an Uncalibrated Environment - Sebastian Van Delden; Frank Hardy (Journal of Systemics, Cybernetics and Informatics, 2008)

(untitled)
The optical flow of high interest points in images of an uncalibrated scene is used to recover the camera orientation of an eye-in-hand robotic manipulator. The system is completely automated, iteratively performing a sequence of rotations and translations until the camera frame is aligned with the manipulator's world frame. The manipulator must be able to translate and rotate its end-effector with respect to its world frame. The system is implemented and being tested on a Stäubli RX60 manipulator using an off-the-shelf Logitech USB camera.